The relationship between customer experience, customer satisfaction, customer trust, and customer loyalty in tourism destination - Muhammad Nurhaula Huddin; Denny Kurnia; D Deviyantoro; N Nafiudin (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This research aims to identify the relationship between customer experience, customer satisfaction, customer trust, and customer loyalty on loyalty tourism destination in Banten Province, Indonesia. This research was conducted using a quantitative approach through an online survey with 299 respondents, with SEM Amos to analyze the data. The results show that customer experience has a positive influence on consume trust, customer satisfaction a positive influence on consumer trust, customer experience has a positive effect on customer loyalty, customer satisfaction a positive effect on customer loyalty and customer trust a positive effect on customer loyalty.